On the properties of linear supply functions in oligopoly - Flavio Delbono; Luca Lambertini (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2015)
In this note we revisit the result by Menezes and Quiggin (2012), showing that under linear supply function competition, the same Nash equilibrium results when arms choose slopes or intercepts of their supply functions. This is because the first order conditions emerging in the two strategy spaces are not linearly independent.
Keywords: D43; L13; 330